Aristokratiske allianser og konflikter i nordisk seinmiddelalder - Erik Opsahl (Collegium Medievale, 2020)
The point of departure is the Swedish rebellion against the regime of King John (Hans) in 1501. Sten Sture the Elder was the rebellion's most prominent leader. The article moves from a discussion of Sten's character and motives for his policy to a more general discussion of the motives of the late medieval Scandinavian aristocracy's political agitation and conduct. The principal question is whether the aristocrats were motived by economic profit and personal career alone, or if other motives, like political and ideological ones, also mattered. Several examples of aristocrats' political choices that cannot have been motivated by economic gains are examined. Thereafter, the article presents the main features of the late medieval aristocracy in Scandinavia as an elite, including its political position, and then especially the balance of power between the aristocracy and the monarch. The conclusion is that the late medieval Scandinavian aristocracy's political behaviour was motivated by a set of motives, that could differ from one situation to another.